2010
DOI: 10.1109/tdei.2010.5539699
|View full text |Cite
|
Sign up to set email alerts
|

Permittivity characteristics of epoxy/alumina nanocomposite with high particle dispersibility by combining ultrasonic wave and centrifugal force

Abstract: This paper proposes a novel technique to fabricate epoxy/alumina nanocomposites with nanoparticle composite process by combination of ultrasonic wave and centrifugal force. The particle dispersion effect of the nanoparticle composite process and its influence on dielectric permittivity were discussed quantitatively. Experimental results clarified that the combination of ultrasonic wave and centrifugal force was effective to increase dispersed nanoparticles and as well as to separate residual agglomerates. We v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In [24], the reduction in 0 r was accompanied by a reduction in the b relaxation, which may imply a reduction in crosslinking density. In the other study [25], the 0 r reduction was more pronounced in the samples prepared following a specific route that included mixing the particles with the resin for 12 h. In this preparation route, any (a) (b) Figure 9 Imaginary relative permittivity of sample E/100H/5SiN at: a different temperatures, and b different water content.…”
Section: Dielectric Spectramentioning
confidence: 81%
See 3 more Smart Citations
“…In [24], the reduction in 0 r was accompanied by a reduction in the b relaxation, which may imply a reduction in crosslinking density. In the other study [25], the 0 r reduction was more pronounced in the samples prepared following a specific route that included mixing the particles with the resin for 12 h. In this preparation route, any (a) (b) Figure 9 Imaginary relative permittivity of sample E/100H/5SiN at: a different temperatures, and b different water content.…”
Section: Dielectric Spectramentioning
confidence: 81%
“…Even in studies that have reported a nanofiller effect on the glass transition, the smaller scale b relaxation was not perturbed [37,43]. On the other hand, other studies [24,25], which investigated the effect of nanofiller on dielectric response of epoxy matrices, claimed that nanofiller inclusion can lead to 0 r values that are lower than the 0 r of both the filler and the host matrix. These studies justified this reduction by postulating a layer of restricted polymer chain mobility around the nanoparticles; however, no experimental exploration has been attempted to validate this proposition.…”
Section: Dielectric Spectramentioning
confidence: 94%
See 2 more Smart Citations
“…We measured the specific gravity of the composite specimens [9]. The specific gravity of the filler  f [g/ml] and particle porosity P [vol%] were obtained as following equations.…”
Section: B Specific Gravity Measurementmentioning
confidence: 99%